Validation of an e-learning 3.0 critical success factors framework: a qualitative research - Miranda, P. (2018)
Aim/Purpose As e-Learning 3.0 evolves from a theoretical construct into an actual solution for online learning, it becomes crucial to accompany this progress by scrutinis-ing the elements that are at the origin of its success. Background This paper outlines a framework of e-Learning 3.0's critical success factors and its empirical validation. Methodology The framework is the result of an extensive literature review and its empirical substantiation derives from semi-structured interviews with e-Learning experts. Contribution The viewpoints of the experts enable the confirmation and the refinement of the original framework and serve as a foundation for the prospective implemen-tation of e-Learning 3.0. Findings The analysis of the interviews demonstrates that e-Learning 3.0 remains in its early stages with a reticent dissemination. Nonetheless, the interviewees invoked factors related to technology, content and stakeholders as being critical for the success of this new phase of e-Learning. Recommendations for Practitioners Practitioners can use the framework as a guide for promoting and implementing effective e-Learning 3.0 initiatives. Recommendation for Researchers As a new phenomenon with uncharted potential, e-Learning 3.0 should be placed at the centre of educational research. Impact on Society The understanding of what drives the success of e-Learning 3.0 is fundamental for its implementation and for the progress of online education in this new stage of its evolution. Future Research Future research ventures can include the design of quantitative and self-administered data collection instruments that can provide further insight into the elements of the framework.